If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 7x = 63 Solving 7x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '7'. x = 9 Simplifying x = 9

| 8x=-16 | | -7x=63 | | 4y+15=6y-11 | | 13k+5=k-7 | | 25h+40=-15h-80 | | 9c-3=17 | | -4a=-1 | | 2y-7y=-100 | | -6x+2=62 | | 4(3x-3)+4=-2(x-4)-2x | | -9=11m-8m | | 3n+14=35 | | 7y-10=11 | | 14=9-x | | 4.6=4m-3.4 | | x+(3x+20)=180 | | 3x+3=-2x-12 | | 6+.10x=.15x+8 | | 2(x-4)+2x=4x-1 | | .15=40+.05 | | .15=40+.05x | | 40+.05x=.15x | | .5x-5=10 | | nx+8=5 | | 2(.5x-5)=20 | | xn+8=5 | | ax-15=15 | | 6m+1=23 | | 6m+1=-23 | | 7y+3=-25 | | 2x-5=2x | | 4(h+2)=3(h-2) | | -2z+4=8 | | 5x+15=40 | | 5-7x=33 | | -2x-4=-10 | | 5x+7+3x=-8+3x | | 4x-20=36 | | 4x-13=-5 | | 20-5x=45 | | 6(4z+12)=3(8z+4) | | 6(4z+2)=3(8z+4) | | -104=8x | | 3+p=8 | | 6+3x=17-2 | | -(8m+4)=4m-2(6m+2) | | -15+n=-9 | | m-9=-13 | | p-6=-5 | | n+16=9 | | 14b=-56 | | 10n=40 | | 3x+14=2x-1 | | 5.5-3b=2b-6.25 | | -15x=0 | | -5(5.25+3.1x)=-6.2(2.5x+1.9) | | 21=-7n | | -126=14k | | 0.2f+0.6(f+20)=-8+0.4f | | (x+3)4=6 | | q-9.6=2 | | -16+x=-15 | | -17=x-15 | | -7+m=8 | | -17x=-204 |